2019
DOI: 10.1016/j.watres.2019.02.038
|View full text |Cite
|
Sign up to set email alerts
|

COD/sulfate ratio does not affect the methane yield and microbial diversity in anaerobic digesters

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…This resulted in predicted maximum total sulfide concentrations of 584, 1193, and 2463 mg S L −1 and maximum undissociated H 2 S concentrations of 181, 247, and 358 mg S L −1 for initial sulfate concentrations of 0.84, 1.68, and 3.34 g S L −1 , respectively. These concentrations are within the wide range of reported sulfide concentrations that trigger toxicity in anaerobic environments (100–1400 mg S L −1 as total sulfide and 50–400 mg S L −1 as H 2 S) (Cetecioglu et al, 2019; Chen et al, 2008, 2014; Giménez et al, 2011; Lu et al, 2016; Maillacheruvu et al, 1993; Zamariolli Damianovic et al, 2016), with the exception of the total sulfide concentration at the 3.34 g S L −1 initial condition, which is well above the range. Thus, it appears that methanogenesis can proceed uninhibited at total sulfide concentrations as high as 2463 mg S L −1 with WAS as the organic substrate.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…This resulted in predicted maximum total sulfide concentrations of 584, 1193, and 2463 mg S L −1 and maximum undissociated H 2 S concentrations of 181, 247, and 358 mg S L −1 for initial sulfate concentrations of 0.84, 1.68, and 3.34 g S L −1 , respectively. These concentrations are within the wide range of reported sulfide concentrations that trigger toxicity in anaerobic environments (100–1400 mg S L −1 as total sulfide and 50–400 mg S L −1 as H 2 S) (Cetecioglu et al, 2019; Chen et al, 2008, 2014; Giménez et al, 2011; Lu et al, 2016; Maillacheruvu et al, 1993; Zamariolli Damianovic et al, 2016), with the exception of the total sulfide concentration at the 3.34 g S L −1 initial condition, which is well above the range. Thus, it appears that methanogenesis can proceed uninhibited at total sulfide concentrations as high as 2463 mg S L −1 with WAS as the organic substrate.…”
Section: Resultssupporting
confidence: 69%
“…They observed that the sulfide inhibition affects acidogenesis the most, while not having a strong effect on the methanogenic step (Polprasert & Haas, 1995). This has been further shown by Cetecioglu et al who found that the digestion of simple substrates such as acetate, propionate, and butyrate using sulfate acclimated sludge was unaffected by SO 4 2— to‐COD ratios as high as 2 g:g, which indicates that sulfide inhibition had no effect on the acetogens and methanogens in those cultures (Cetecioglu et al, 2019). However, other studies report methanogens are the most inhibited by sulfide toxicity (Oleszkiewicz et al, 1989; Shin et al, 1995).…”
Section: Introductionmentioning
confidence: 68%
“…Nevertheless, control of the manipulation mechanism depends on thermodynamic and metabolic principles: the product mixture is specified by thermodynamic constraints and enzyme availability in pure culture fermentation, while, it is more complicated in mixed culture fermentation because of the wide range of metabolic activities and energetic considerations (Mohd-Zaki et al, 2016). Many studies have been conducted to identify metabolic flux and energy conversions in mixed culture fermentation (Lee et al, 2008;Hoelzle et al, 2014;De Vrieze and Verstraete, 2016;Cetecioglu et al, 2019). Lee et al (2008) evaluated H 2 production from glucose fermentation under several pH conditions, thermodynamically (Lee et al, 2008).…”
Section: Volatile Fatty Acid Composition Shift At the Bioaugmented Reactormentioning
confidence: 99%
“…These mixed communities offer the advantage of protecting the microbial species of interest (e.g., metal respires or methanogens) against the toxic environment of the industrial effluent. However, on the other side, mixed communities also result in competition between various bacterial groups, some having better fitness and thermodynamics than the ones of interest for resource recovery (e.g., more thermodynamically adapted sulphate-reducing bacteria vs methanogens or metal oxidisers) (Hoelzle et al 2014;Cetecioglu et al 2019;Tang et al 2019).…”
Section: Barriersmentioning
confidence: 99%